Pemahaman Dasar Hukum Perjanjian Hibah Melalui Penyuluhan di Desa Tempos, Kecamatan Gerung, Lombok Barat - Rinda Philona; I Made Suradana; Novita Listyaningrum Listyaningrum (Universitas Mataram, 2020)
Cooperation aims to import knowledge and understanding to the Tempos village people on the basic understanding of the law and grant convenant. Training is held by the cooperation of various parties: the combined small farm groups of tempos village and teachers of the law faculty of the university of 45 Mataram. Summary of counseling is conducted by the method of speech and discussion. All the supervisors followed the program in a fine way until it was finished and could even be said to be very enthusiastic by giving questions that olchs own village people of tempos had so far been able to conclude that the execution of this law was good and successfull in which the material could be handled so well